2019
DOI: 10.1080/10872981.2019.1630239
|View full text |Cite
|
Sign up to set email alerts
|

Creating assessments as an active learning strategy: what are students’ perceptions? A mixed methods study

Abstract: Background: Teaching students how to create assessments, such as those involving multiplechoice questions (MCQs), has the potential to be a useful active learning strategy. In order to optimize students' learning, it is essential to understand how they engage with such activities. Objective: To explore medical students' perceptions of how completing rigorous MCQ training and subsequently writing MCQs affects their learning. Design: In this mixed methods exploratory qualitative study, eighteen second-year medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 35 publications
5
35
1
1
Order By: Relevance
“…Furthermore the time taken could suggest that MCQ-writing had a high task complexity for the students and they needed greater instructional support (Leppink and Duvivier, 2016). In an learning activity where medical students wrote MCQs for assessment in small groups, Kurtz et al (2019) reported the task required a high level of content knowledge, and more problem-solving and content-integration than other study methods. Compared to other implementations of MCQ activities, our course requirements may have been too high for the effort required by students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore the time taken could suggest that MCQ-writing had a high task complexity for the students and they needed greater instructional support (Leppink and Duvivier, 2016). In an learning activity where medical students wrote MCQs for assessment in small groups, Kurtz et al (2019) reported the task required a high level of content knowledge, and more problem-solving and content-integration than other study methods. Compared to other implementations of MCQ activities, our course requirements may have been too high for the effort required by students.…”
Section: Discussionmentioning
confidence: 99%
“…MCQ writing for question banks has also been reported as a small group learning activity for medical students, who report this as an enjoyable and useful learning activity (Gooi and Sommerfeld, 2015;Harris et al, 2015;Lawrence, Famokunwa and Ziff, 2016). However MCQ writing may be less efficient than other learning methods (Kurtz et al, 2019) and have high cognitive load for students (Grainger et al, 2018). Our pilot of an MCQ authoring and answering exercise had variable student acceptance (Grainger et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…To conclude, as highlighted by Kurtz et al [1], creating assessments, particularly with MCQs, can be beneficial for students' active learning. Students find revising topics through practising questions useful [2] and therefore could benefit further from designing questions.…”
mentioning
confidence: 83%
“…The mixed methods study highlighted that students found writing questions a beneficial tool [1]. However, there were concerns that this was time-consuming and, for this reason, students should have maximum benefit from questions they design.…”
mentioning
confidence: 99%
See 1 more Smart Citation